Implementasi Peraturan Bupati Gunungkidul Nomor 36 Tahun 2015 Tentang Pencegahan Perkawinan Pada Usia Anak dalam Perspektif Maslahah Mursalah - Affaruddin, Agung Ilham; Nadhifah, Nurul Asiya (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2019)
Regent Regulations (Perbup) of Gunungkidul Number 36 Year 2015 Concerning Prevention of Marriage at the Age of Child is a special regulation regarding the efforts, programs, actions, activities used by the government agencies of Gunungkidul Regency in order to prevent and reduce the number of marriages at the age of child. Wonosari Religious Court statistics show a decrease in the number of submissions for marriage dispensations from 2015 to 2017 after the enactment of this regulation. In 2015 there were 109 cases of marriage dispensation, in 2016 there were 85 cases of marriage dispensation, in 2017 there were 65 cases of marriage dispensation. In its implementation, this regulation has benefits because it forms the basis of human life (maslahah dharuriyyah). This regulation has also answered the problems that humans need to eliminate the difficulties they face (maslahah hajiyyah). In addition, this regulation has preserved the wisdom and goodness of manners and social and cultural beauty (maslahah tahsiniyyah). Seen from its implementation, Perbup Gunungkidul Number 36 of 2015 concerning Prevention of Marriage at the Age of Child is in accordance with the principles of problem solving. [Implementasi Perbup Gunungkidul Nomor 36 Tahun 2015 Tentang Pencegahan Perkawinan Pada Usia Anak merupakan peraturan khusus berupa upaya-upaya, program, aksi, kegiatan yang digunakan instansi pemerintahan Kabupaten Gunungkidul dalam rangka mencegah terjadinya perkawinan pada usia anak dan menurunkan angka perkawinan pada usia anak. Peraturan ini memiliki sisi kebaikan dan kemanfaatan dimana peraturan ini memang telah menjadi dasar tegaknya kehidupan asasi manusia (maslahah dharuriyyah), peraturan ini juga telah menjawab persoalan yang dibutuhkan manusia untuk menghilangkan kesulitan dan kesusahan yang dihadapi (maslahah hajiyyah), selain itu peraturan ini telah memelihara kebagusan dan kebaikan budi pekerti serta keindahan sosial budaya (maslahah tahsiniyyah). Sesuai dengan penelitian ini maka Perbup Gunungkidul Nomor 36 Tahun 2015 Tentang Pencegahan Perkawinan Pada Usia Anak telah sesuai dengan prinsip-prinsip maslahah mursalah. Oleh sebab itu, maka disarankan peraturan ini bisa dijadikan percontohan untuk ditiru dan diterapkan oleh daerah di sekitarnya baik secara skala dalam provinsi maupun skala luar provinsi se-Indonesia.]